ONLINE ACROSTIC TECHNIQUES IN INCREASING THE POETRY WRITING SKILLS OF CLASS X STUDENTS IN THE INDEPENDENCE CURRICULUM - Radina Amalia; Ani Mukoliyah (International Journal of Education and Literature, 2023)
One of the main focuses of the Merdeka Curriculum is literacy skills. Indonesian is a subject that teaches literacy skills, one of which is the sub-aspect of writing poetry. The purpose of this study was to determine the effectiveness of the acrostic technique in improving the poetry writing skills of class X at SMKN 1 Magetan. The research method used is a quantitative research that compares the results between the two cycles. The results of the study found that the acrostic technique increased students’ poetry writing skills. Based on the findings, the researcher suggestthator teachers use the acrostic technique as an alternative method of teaching poetry writing skills because it has been proven to be able to improve students’ competence and learning activities.